1996
DOI: 10.1097/00005053-199608000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Major Depressive Disorder in Taiwan Defined by the Chinese Diagnostic Interview Schedule

Abstract: The lifetime prevalence rate of major depressive disorder (MDD), as defined by the Chinese Diagnostic Interview Schedule, is 1.14% in Taiwan. This is significantly lower than the lifetime prevalence rates reported in Western studies and similar to other studies in the Chinese population using similar methods for assessing cases of MDD. Epidemiological data from 136 MDD cases were analyzed to provide possible explanations for this difference in lifetime prevalence rates. The low rate of broken families in Chine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 17 publications
2
30
1
1
Order By: Relevance
“…The lower prevalence of MDD in Asians might partly be accounted for by underreporting due to cultural reluctance to endorse symptoms, by depressive symptoms being expressed as somatic symptoms, by greater resilience, by availability of more social support in Asian societies or by higher tolerance of symptoms and disease. 53,62,63,130 It is remarkable that the studies carried out in the eldest age groups appeared to have the highest ORs for the association of the BDNF Val66Met polymorphism with MDD ( Figures 2a and b: Hwang et al 42 and Taylor et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower prevalence of MDD in Asians might partly be accounted for by underreporting due to cultural reluctance to endorse symptoms, by depressive symptoms being expressed as somatic symptoms, by greater resilience, by availability of more social support in Asian societies or by higher tolerance of symptoms and disease. 53,62,63,130 It is remarkable that the studies carried out in the eldest age groups appeared to have the highest ORs for the association of the BDNF Val66Met polymorphism with MDD ( Figures 2a and b: Hwang et al 42 and Taylor et al…”
Section: Discussionmentioning
confidence: 99%
“…Lower lifetime prevalence of MDD has been observed in Chinese, Japanese and Korean populations. 62,63 Cross-national epidemiologic surveys indicated that the lifetime prevalence of MDD is 1.5% in Taiwanese and 2.9% in Koreans, 53 compared to a mean of 15-17% in Western populations. 50,52,64 Although a number of the studies mentioned above have suggested the Met allele to be the risk allele for depression, the higher frequency of the Met allele in Asians in the presence of lower MDD prevalence rates might suggest that the Met allele protects against MDD.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, studies of East Asian samples indicated that the Val allele is associated with better cognitive function (Cheon et al 2008;Yeh et al 2009;Wang et al 2013). Considering the converse association findings of cognitive function mentioned above with COMT Val158Met in Caucasians and East Asians (Palmatier et al 1999) and the difference in the lifetime prevalence rate of MDD in Western vs. East Asian countries (Kessler et al 1994;Hwu et al 1996;Parker et al 2007), it is plausible to assume that the variant potentially involves MDD pathogenesis with ethnic differences, which may contribute to the inconsistency of previous findings.…”
Section: Introductionmentioning
confidence: 95%
“…Depressive disorder is another well-known chronic, recurrent and disabling mental disease with high direct and indirect costs to society in both western and eastern cultures (Hwu et al, 1996;Cassano and Fava, 2002;Lu. et al, 2008).…”
Section: Introductionmentioning
confidence: 99%